Quorum Sensing and the Transition from Symbiosis to Dysbiosis in Periodontal Biofilms: A Scoping Review - Felisha Febriane Balafif; Anggun Rafisa; Faisal Kuswandani; Nuroh Najmi (Jurnal EduHealth, 2025)
Introduction: Quorum sensing (QS), a bacterial cell communication system, has emerged as a key regulator of community level biofilm dynamics, yet its role in mediating this ecological transition has not been systematically synthesized. This scoping review aimed to map and synthesize evidence published over the last decade on the role of quorum sensing in driving the transition from symbiosis to dysbiosis in periodontal biofilms. Methods: A scoping review was conducted in accordance with the PRISMA-ScR guidelines. Searches were performed in PubMed, Scopus, and Web of Science for studies published between 2016 and 2025 that investigated quorum sensing mechanisms in periodontal or subgingival biofilms using in vitro, ex vivo, or in vivo models. Data were charted and analyzed descriptively. Results: Sixty one studies met the inclusion criteria. Autoinducer-2 mediated signaling emerged as the most consistently reported quorum sensing pathway in periodontal biofilms. Quorum sensing was shown to regulate interspecies communication, biofilm maturation, metabolic cooperation, and coordinated virulence expression. Evidence indicated that quorum sensing primarily drives dysbiosis through functional reprogramming of microbial communities rather than through numerical dominance of specific pathogens. Several studies also linked quorum sensing activity to enhanced host inflammatory responses and alveolar bone loss in experimental models. Conclusion: Quorum sensing as a central ecological mechanism orchestrating the transition from symbiosis to dysbiosis in periodontal biofilms. By coordinating community wide microbial behavior, host and microbe interactions, quorum sensing contributes to sustained dysbiosis and periodontal inflammation.